What works in crime prevention and rehabilitation: an assessment of systematic reviews - Weisburd, David (Criminology & public policy, 2017)
Just four decades ago, the predominant narrative in crime prevention and rehabilitation was that nothing works. Since that time, criminologists have accumulated a wide body of evidence about programs and practices in systematic reviews. In this article, we summarize what is known in seven broad criminal justice areas by drawing on 118 systematic reviews. Although not everything works, through our “review of reviews,” we provide persuasive evidence of the effectiveness of programs, policies, and practices across a variety of intervention areas.